LA INTERVENCIÓN EN EL TEMPLO DE SANTA ANA DEL CUSCO - Zecenarro Benavente, Germán (2017)
This article addresses and explains the critical analysis of the conservation and restoration interventions carried out by the Ministry of Culture (in the period between 2006 and 2012) in the Santa Ana Church of Cusco (Peru). The achievements are weighed, as well as the coherence of its results and achievements, and their absences in terms of the restitution of the full conception of the building. This is done in order to have a body of methodological experiences that express the aspects that led to the comprehensive recovery of its material testimonies and the implicit values of the monument, within the panorama of the patrimonial conservation realized in the city of Cusco and the region. This article analyzes the aspects of the intervention that enabled the recovery of the volumetrics and the interior space of the monument. It also observes the lack of proposals about the space of the temple’s atrium, which could have been articulated from the point of view of management, with projects for the recovery of the adjacent urban environment undertaken by the municipal authority.